Design of Discovery Learning-Based Student Worksheets on Environmental Change Material for 10th Grade Senior High School - Febriani, Rizka Ambar; Sari, Tika Mayang (Fakultas Tarbiyah dan Ilmu Keguruan UIN Jurai Siwo, Lampung, 2024)
One of the issues encountered in high school education is the limited teaching materials that facilitate students in enriching their experiences, building knowledge and engagement, and supporting problem-solving skills. This study aims to develop discovery learning-based student worksheets on environmental change material. The research method used is Research and Development (R&D), adopting the 4D model: Define, Design, Develop, and Disseminate. the data analysis used includes quantitative and qualitative analysis. The study used two types of validation: media expert and material expert. Validation results indicate that the worksheets developed is valid and suitable for trial, with media validation at 83% and material validation at 84%. The trial results show a student response rate of 89% and a teacher response rate of 99%, indicating that the discovery learning-based worksheets on environmental change is practical for use in teaching.